Network democracy : conservative politics and the violence of the liberal age - Giesbrecht, Jared, 1979- (McGill-Queen's studies in the history of ideas, 2017)
A unique hybrid of ancient and contemporary conservative thought that offers a radical challenge to Western liberalism.